Detection of carbamyl phosphate synthetase 1 deficiency using duodenal biopsy samples. Issue 4 (April 1980) - Hoogenraad, N J; Mitchell, J D; Don, N A; Sutherland, T M; Mc Leay, A C
Abstract : The activity of urea cycle enzymes was assayed in duodenal biopsy specimens obtained from a female infant who presented with neonatal hyperammonaemia. All enzyme levels were normal except N-acetyl glutamate-dependent carbamyl phosphate synthetase 1 (CPS1) which was half the mean activity in normal control specimens. A similar deficiency of CPS1 was also shown in duodenal specimens from the patient's mother who became slightly symptomatic after relatively high protein meals and during pregnancy, and had spontaneously modified her diet to one with protein restriction. The patient is growing normally on a dietary regimen similar to that spontaneously adopted by her mother. Urea cycle enzyme activity in the duodenal biopsy material from the controls was similar to that found in the normal human liver and appears to have distinct advantages as a means of assaying for urea cycle defects in patients with hyperammonaemia and their relatives.